FROM SLAVERY TO SALVATION: A STUDY ON ABDULRAZAK GURNAH’S PARADISE (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACTThe paper “From Slavery to Salvation: A Study on Abdulrazak Gurnah’s Paradise” describes the challenges and difficulties Yusuf has come through to attain his salvation from the state of slavery in his life. He turns his struggles a tool to reach his salvation. Though he gives important to education, personal relationship, and self –discovery, this paper concentrates the salvation of Yusuf, which makes him aware his purpose of life and mould himself a bold enough person to take his own decision. He believes that, salvation is not possible without struggles it ultimately allows Yusuf to find peace.